Meningkatkan Kemampuan Sosial Emosional Anak Usia Dini melalui Permainan Petak Umpet di TK Karya Bunda Mandiri - Khadijah, Khadijah; Sari, Sinta Affriliana; Risnawati, Risnawati; Siregar, Jihan Fadiyah Fitri; Azmi, Nurul (AS-SABIQUN, 2023)
This study aims to investigate the potential of hide-and-seek games as a tool in improving social-emotional abilities in early childhood. Improving social-emotional abilities is an important goal in Early Childhood education interventions because children's social-emotional development is often hampered. In this study researchers used an approach based a hide-and-seek game that attracts children's interest and utilizes the social-emotional concepts involved in this game, such as developing interaction skills, the ability to work together in groups and the ability to manage emotions. The research method used involved participants in the apple group at Karya Kindergarten Mandiri mothers with an age range of 4-5 years arranged in an intervention group. Researchers provide a scaled structured hide-and-seek game session in which children will be given the opportunity to participate in games and apply previously learned emotional social skills. Researchers also use various supporting strategies such as role models, positive reinforcers and tailored feedback in shaping children to understand and use desired social emotional skills. The results of the study showed a significant increase in children's social emotional abilities after participating in a game-based intervention of hide and seek .Children show improvement in the ability to interact with peers, understand and express their emotions better and work effectively in groups.In addition, hide-and-seek games also show effectiveness in increasing children's involvement in group activities, which can increase children's motivation and reduce the level of social anxiety in children.